Optimizing Pelton Turbine Efficiency through Variable Flow Rates: An Experimental Study - Rahmad Hidayat Boli; Rifaldo Pido; Wawan Rauf (The Indonesian Institute of Science and Technology Research, 2026)
This study experimentally investigates the efficiency characteristics of a laboratory-scale Pelton turbine under variable water flow rates and mechanical loading conditions. Five flow rates (0.04 m³/s, 0.035 m³/s, 0.029 m³/s, 0.024 m³/s, and 0.021 m³/s) were tested by measuring rotational speed, torque, shaft power, and turbine efficiency. The results reveal a nonlinear relationship between load and efficiency for all tested flow rates, with maximum efficiency occurring at intermediate loading conditions. The highest efficiency of 52.727% was obtained at a flow rate of 0.04 m³/s and a load of 12 kg. Were associated with reduced efficiency, which is commonly linked to decreased jet momentum. These findings provide experimental insight into Pelton turbine performance under non-design operating conditions at laboratory scale.